Portrayals of the British militia, 1852–19161. Issue 252 (7th March 2018) - Bennett, Mark
Abstract: This article explores how perceived inefficiencies and inadequacies in the militia were reflected in contemporary works of fiction and satire. The militia's public image was consistently poor: half‐trained battalions, staffed by inefficient senior officers, chronically short of subalterns and recruiting from the very worst elements of the working class. It suffered from the combined flaws of both regulars and volunteers, but was unable to benefit from either the Christian 'civilizing mission' of the former or the earnest patriotic enthusiasm of the latter. This negative image contributed to the ease with which the force was abolished after the Boer War.